2020
DOI: 10.26686/wgtn.13315877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High school students’ experience of online learning during Covid-19: the influence of technology and pedagogy

Abstract: No description supplied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
1
9
1
2
Order By: Relevance
“…Likewise, Yates et al. (2020)’s study in high school students also revealed that over half of the students preferred in‐class collaboration over online collaboration as they value the immediate support and the proximity to teachers and peers from in‐class interaction.…”
Section: Literature Reviewmentioning
confidence: 98%
See 4 more Smart Citations
“…Likewise, Yates et al. (2020)’s study in high school students also revealed that over half of the students preferred in‐class collaboration over online collaboration as they value the immediate support and the proximity to teachers and peers from in‐class interaction.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Therefore, integration of social interaction into pedagogy for online learning is essential, especially at the times when students do not actually know each other or have communication and collaboration skills underdeveloped (Garrison et al., 2010; Gašević et al., 2015). Unfortunately, existing evidence suggested that online learning delivery during the COVID‐19 pandemic often lacks interactivity and collaborative experiences (Bączek et al., 2021; Yates et al., 2020). Bączek et al., (2021) found that around half of the medical students reported reduced interaction with teachers, and only 4% of students think online learning classes are interactive.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations